A robust evaluation of TDP-43, poly GP, cellular pathology and behavior in an AAV-C9ORF72 (G4C2)66 mouse model - Emily G. Thompson; Olivia Spead; Suleyman C. Akerman; Carrie Curcio; Benjamin L. Zaepfel; Erica R. Kent; Thomas Philips; Balaji G. Vijayakumar; Anna Zacco; Weibo Zhou; Guhan Nagappan; Jeffrey D. Rothstein (Acta Neuropathologica Communications)
Abstract The G4C2 hexanucleotide repeat expansion in C9ORF72 is the major genetic cause of both amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) (C9-ALS/FTD). Despite considerable efforts, the development of mouse models of C9-ALS/FTD useful for therapeutic development has proven challenging due to the intricate interplay of genetic and molecular factors underlying this neurodegenerative disorder, in addition to species differences. This study presents a robust investigation of the cellular pathophysiology and behavioral outcomes in a previously described AAV mouse model of C9-ALS expressing 66 G4C2 hexanucleotide repeats. The model displays key molecular ALS pathological markers including RNA foci, dipeptide repeat (DPR) protein aggregation, p62 positive stress granule formation as well as mild gliosis. However, the AAV-(G4C2)66 mouse model in this study has marginal neurodegeneration with negligible neuronal loss, or clinical deficits. Human C9orf72 is typically associated with altered TAR DNA-binding protein (TDP-43) function, yet studies of this rodent model revealed no significant evidence of TDP-43 dysfunction. While our findings indicate and support that this is a highly valuable robust and pharmacologically tractable model for investigating the molecular mechanisms and cellular consequences of (G4C2) repeat driven DPR pathology, it is not suitable for investigating the development of disease- associated TDP-43 dysfunction or clinical impairment. Our findings underscore the complexity of ALS pathogenesis involving genetic mutations and protein dysregulation and highlight the need for more comprehensive model systems that reliably replicate the multifaceted cellular and behavioral aspects of C9-ALS.